Ecological Quality Status of the Algiers coastal waters by using macroalgae assemblages as bioindicators (Algeria, Mediterranean Sea) - CHABANE, KHADIDJA; BAHBAH, LAMIA; SERIDI, HALIMA (Mediterranean Marine Science, 2018)
Macroalgae assemblages have been used as a quality element for the assessment of the Ecological Status Classes (ESC) of coastal water bodies for the implementation of the European Water Framework Directive (WFD, 2000/60/EC). To assess the suitability of this quality element in Algiers coasts, seven sampling sites with five (5) replications covering a wide range of anthropogenic pressures were studied during spring and summer 2015. Coverage data of macroalgae in each sampling site were analyzed on species, i.e., structural (species number, nMDS, clustering, K-dominance and Simper analysis on Bray–Curtis similarity) and on Ecological Status Groups, i.e., functional (nMDS, clustering, K-dominance, Ecological Evaluation Index/EEI-c) biological levels. Key water variables (temperature, salinity and pH) along with the anthropogenic stress index MALUSI were also estimated. The obtained results revealed a significant effect of anthropogenic stress in the macroalgal assemblages. The structural analysis showed: (1) species richness of 86 taxa in total, (2) dominance of Cystoseira amentacea var. stricta (late-successional) associated by Lithophyllum incrustans, and Jania rubens in non-impacted sites and of Ulva rigida, Ulva intestinalis and Caulerpa cylindracea (opportunistic) species in impacted sites, and (3) record a higher proportion of low abundance of species in polluted communities than in less polluted communities. The functional analysis showed: (1) classification of sites based on multivariate and K-dominance analyses in four groups, three in agreement with water degradation, and one for low salinity influence, (2) classification of sites into “Bad”, ”High”, “Moderate” and “Good” ESC’s by EEI-c index, (3) a strong non-linear relationship (R²=0.85) of EEI-c index with MALUSI index. Therefore, to implement a national monitoring program within the scope WFD in Algeria coasts, the EEI-c index will be a suitable tool.